Principles of Osteoimmunology Molecular Mechanisms and Clinical Applications - Pietschmann, Peter (Springer International Publishing : Imprint: Springer, 2016)
This fully updated and extended second edition provides a comprehensive overview on the basic concepts of the rapidly developing field of osteoimmunology and also offers in-depth insights into the molecular mechanisms of bone diseases. Clinical data is presented and put into context with the latest research findings. This second edition in addition discusses the latest topics in transplantation immunology. The book addresses scientists and physicians working in immunology, pathophysiology and osteology.